Trend of adjusted antenatal care visits on pregnant women and neonatal during the COVID-19 pandemic: Findings from a three districts survey in 2021 - Ibrahim, Juliani; Takahata, Yoko; Ibrahim, Sukaeni (Al-Sihah: The Public Health Science Journal, 2025)
Sustainable health development efforts amid infectious disease outbreaks such as Coronavirus disease 2019 (COVID-19) require a resilient maternal health system. With cases rising globally and across Asia, Indonesia faces significant disruptions in essential services. A critical research gap exist in utilizing adjusted time-series analysis to isolated pandemic impact from seasonal variation in urban Indonesia. This study evaluates trends in antenatal care (ANC) visits (January 2019–December 2020) at three Community Health Centres in Makassar: Bara-Baraya, Jongaya and Batua using Interrupted Time Series (ITS) analysis. Findings reveal a significant decline in visits during the second and third quarters of 2020, primarily due to transmission fears. We suggest integration of telemedicine and home visits to maintain continuity of care. Although focused on urban Makassar, these results are an important reference for health and offer applicable solutions for other developing countries facing resource constraints. This study emphasizes the need for inclusive prevention strategies to protect maternal health in urban and rural areas in low- to middle-income countries during systemic health crises.